Advances in Wind Energy and Wind Turbines (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The subject of this reprint covers the latest research in the field of wind energy methods and technologies. The results of work on modeling and optimization of wind turbines, their location, methods of monitoring and diagnostics, and development prospects were presented. Contemporary problems, dangers and risks in the field of wind engineering were also pointed out.